Exploring teaching of scientific reasoning and argumentation in psychology education: the central role of epistemology - Evers, Marleen; Elen, Jan; Vandecandelaere, Machteld (Pedagogische studiën, 2025)
Scientific reasoning and argumentation (SRA) are complex thinking skills enabling students to evaluate, generate, and use information that helps to understand and solve scientific and societal challenges. Unlike in hard sciences and history education, teaching SRA in psychology education is understudied. This is problematic as SRA-skills are highly discipline-specific and can help students to cope with the characteristics of psychology as ill-structured and nonparadigmatic discipline. Therefore, the aim of this exploratory study was to identify key issues in teaching SRA in psychology education. Fifteen secondary psychology teachers participated in three focus groups. An inductive thematic analysis identified three key themes which show that (1) teachers' ambitions for psychology education, (2) the ways in which teachers understand SRA, and (3) teachers' epistemological beliefs, help to understand the reported difficulties in teaching SRA in psychology. The strong epistemological dimension of SRA was not easily recognized by teachers, nor did teachers refer to epistemological criteria when discussing assessment criteria, making it difficult for teachers to see how to assess SRA. The study indicates that teachers’ epistemological beliefs (e.g. psychology is vague and subjective) may explain this difficulty. The results can serve as starting point for further research on SRA in psychology education.